2016
DOI: 10.18388/abp.2015_1070
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional predictors of mortality in prevalent peritoneal dialysis patients.

Abstract: Malnutrition remains one of the major predictors of mortality in peritoneal dialysis (PD) patients. The aim of the study was to evaluate the nutritional status of prevalent PD patients, and to determine the best predictors of outcome among anthropometric and laboratory indices of nutrition. The study included 106 prevalent PD patients from a single university-based unit. Anthropometric assessment at baseline included: body mass, body mass index (BMI), skinfold thickness, lean body mass (LBM), content of body f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
3
9
0
1
Order By: Relevance
“…Many studies have found that albumin was a strong predictors for dialysis patients [25,26]. Our study also confirmed that serum albumin, no matter baseline level or time-dependent one, could strongly predict the clinical outcome of hemodialysis patients.…”
Section: Discussionsupporting
confidence: 85%
“…Many studies have found that albumin was a strong predictors for dialysis patients [25,26]. Our study also confirmed that serum albumin, no matter baseline level or time-dependent one, could strongly predict the clinical outcome of hemodialysis patients.…”
Section: Discussionsupporting
confidence: 85%
“…Similar data have been obtained by researchers from Greece [10]. Malgorzewicz S. and co-authors also determine serum albumin decrease, total cholesterol increase, and a low index of arm muscle circumference are the main NS parameters that have a negative effect on survival [15]. Leinig C. and co-authors in their work have determined that higher body mass index contributes to better survival of patients of dialysis patients' population [11].…”
Section: Completesupporting
confidence: 65%
“…Basing on an examination of 199 PD patients, the authors stated that low serum albumin level, subjective global assessment (SGA), and an insufficient amount of calories taken according to dietary diaries are the main markers of nutritional disorders associated with a veritable increase of mortality and survival rates [11]. Basing on laboratory, functional and anthropometric methods of NS assessment researchers have confirmed the available data concerning the prevalence of ND and their negative impact on the survival of ESRD patients treated with PD [15]. The received data show that the PD treated patients' survival rate is apparently higher in groups with normal NS or a light degree of ND (χ 2 = 22.9; df = 3; p = 0.00004).…”
Section: Completementioning
confidence: 95%
See 1 more Smart Citation
“…Associado ao melhor controle das infecções, estudos que avaliaram e orientaram a adequação do balanço hídrico, da nutrição e especialmente da sobrecarga de glicose, também contribuíram para aumentar a sobrevida dos pacientes em DP (9)(10)(11)(12)(13)(14).…”
Section: Introductionunclassified